How to go beyond C1 products with electrochemical reduction of CO2. Issue 23 (4th November 2021) - Li, Da; Zhang, Hao; Xiang, Hang; Rasul, Shahid; Fontmorin, Jean-Marie; Izadi, Paniz; Roldan, Alberto; Taylor, Rebecca; Feng, Yujie; Banerji, Liam; Cowan, Alexander; Yu, Eileen Hao; et al.
Abstract : This review summaries recent development across electro-, photoelectro- and bioelectro-catalyst developments for multi-carbon products from CO2 . It also explores the role of device design and operating conditions in enabling C–C bond generation. Abstract : The electrochemical reduction of CO2 to produce fuels and value-added organic chemicals is of great potential, providing a mechanism to convert and store renewable energy within a carbon-neutral energy circle. Currently the majority of studies report C1 products such as carbon monoxide and formate as the major CO2 reduction products. A particularly challenging goal within CO2 electrochemical reduction is the pursuit of multi-carbon (C2+ ) products which have been proposed to enable a more economically viable value chain. This review summaries recent development across electro-, photoelectro- and bioelectro-catalyst developments. It also explores the role of device design and operating conditions in enabling C–C bond generation.